Strategi Media Sosial dalam Meningkatkan Kesetaraan Gender Bagi Perempuan: Analisis Wacana Kritis di Instagram @Magdaleneid - Dandi Saputra; Naurah Lisnarini (Jurnal Humanitas: Katalisator Perubahan dan Inovator Pendidikan, 2023)
Gender equality still needs to be upheld in Indonesia, considering that the country's Gender Equality Index for 2021 is only 111 and its implementation has not been impactful. The ancient belief that men are taller than women is biased. Therefore, there should be a greater emphasis on understanding and implementing gender equality regulations within the community, especially through the media utilization. This research aims to describe the role of Instagram in voicing gender equality through the @magdaleneid account. The qualitative method used is a critical paradigm that analyzes crisis discourse obtained from the @magdalne.id account. The analysis process employs Sara Mills' critical discourse analysis at the levels of words, sentences, and discourse. The study results show  results two dominant types of content published on the account: education and support for the progressive feminist movement that aims to achieve gender equality for women. The language used in this content shows affection for women, promotes appropriate education, and encourages the voicing of gender equality. The discourse level applied involves using of colors, characters, and animations that align with the message.